Architectural Knitted Windbreaks for Improved Wind Comfort in the City: A Wind Tunnel Study of Custom-Designed Porous Textile Screens - Erica Hörteborn; Malgorzata A. Zboinska; Valery Chernoray; Mats Ander (Buildings, 2022)
There is a need to shield from the wind to improve pedestrian comfort in urban environments. Perforated windbreaks, such as fences, vegetation or textile nets, have proven to be an efficient solution, whereas knitted textiles have not yet been explored. The purpose of this study was to evaluate the capacity of knitted textile windbreaks to reduce wind velocities, to inform further research and promote wider architectural applications. Five custom-knitted textile prototypes, representing fragments of textile windbreaks, were tested in a wind tunnel and compared against a perforated and a nonperforated solid board. Forces on the models, as well as upstream and downstream velocities, were measured. The results indicate that the optimal optical porosity of knitted windbreaks should be around 10%, which differs from the porosity for perforated windbreaks recommended by prior studies. Moreover, it was observed that a textile windbreak knitted using the drop-stitch technique efficiently reduces the wind, while not generating a large drag force. Furthermore, the drag coefficient for the knitted windbreak is reduced with increased windspeed. With this, the presented study demonstrates that knitted structures exposed to wind influence have the functional potential of becoming efficient windbreaks, thus improving wind comfort and aesthetic user experience in the urban space.